2021
DOI: 10.1111/aos.14862
|View full text |Cite
|
Sign up to set email alerts
|

Measuring optic nerve head perfusion to monitor glaucoma: a study on structure–function relationships using laser speckle flowgraphy

Abstract: Purpose We aimed to describe the global and localized correlations among visual field (VF) sensitivity, optic nerve head (ONH) perfusion measured by laser speckle flowgraphy (LSFG) and neural structure measured by optical coherence tomography (OCT) in open‐angle glaucoma (OAG) and to compare the floor effect for LSFG and OCT. Methods Cross‐sectional, multicenter study including one eye each from fifty OAG patients (mean age 69.3 years; average VF mean deviation, MD, −8.5 dB, range −25.17 to 0.85 dB) and fifty‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 56 publications
(112 reference statements)
2
16
0
Order By: Relevance
“… 12 In glaucoma, the usefulness of OCTA-based vascular metrics has been demonstrated in the discrimination of diseased eyes from healthy eyes. 13 15 Relating structural and, increasingly, vascular 16 25 changes with functional loss of vision in glaucoma is referred to as the structure–function relationship. 26 28 …”
mentioning
confidence: 99%
“… 12 In glaucoma, the usefulness of OCTA-based vascular metrics has been demonstrated in the discrimination of diseased eyes from healthy eyes. 13 15 Relating structural and, increasingly, vascular 16 25 changes with functional loss of vision in glaucoma is referred to as the structure–function relationship. 26 28 …”
mentioning
confidence: 99%
“…Using ANOVA, we found that MBR-overall, MBR-vessel, and MBR-tissue were lower in eyes with more severe active TED. The MBR can quantitatively measure blood flow velocity of the ONH in LSFG examinations ( 14 , 15 ). Lower MBRs may indicate slower ONH blood flow velocities in patients with more severe active TED.…”
Section: Discussionmentioning
confidence: 99%
“…Laser speckle flowgraphy (LSFG) is based on the laser speckle phenomenon and is a noninvasive instrument that can measure two-dimensional relative blood flow velocity of the ocular microcirculation in real time ( 12 , 13 ). The mean blur rate (MBR), which represents the velocity of optic nerve blood flow, has been previously applied to monitor the severity of glaucoma ( 14 , 15 ), evaluate ischemic optic neuropathy ( 16 , 17 ), and detect retinal diseases ( 18 ). Although LSFG can be used to estimate optic nerve blood flow, to the best of our knowledge, it has never been used to monitor blood flow changes in patients with TED or to evaluate the severity of TED.…”
Section: Introductionmentioning
confidence: 99%
“…An elliptical region of interest (ROI) was drawn in a semi-automated fashion to fit the ONH borders, having as a reference the color fundus photograph, as previously described. 25 Within each ROI, the mean perfusion in the ONH microvasculature (referred to as Mean Tissue [MT]) was calculated using the “Cross-section” automated segmentation tool of the software. The mean of two scans was then averaged.…”
Section: Methodsmentioning
confidence: 99%